2013
DOI: 10.4172/2155-9554.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Tumor Necrosis Factor-Alpha, Interleukin-6, and Interferon- Gamma during the Active Phases of Bechet’s Disease, Pustular Psoriasis, Palmoplantar Pustulosis, and Stevens-Johnson Syndrome: A Pilot Study

Satoshi Nakamura

Abstract: Inflammatory serum cytokines are produced by lymphocytes and target organs in inflammatory skin diseases. Changes in cytokines fluctuate daily during disease activity. Comparisons of serum cytokine levels, cytokine species, or flow cytometric changes during the disease course might not be adequate. In addition, daily target organ examinations are difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The present study found a significant positive correlation between serum levels of TNF-a and PASI score (P = 0.03); this result is in agreement with that of some investigators [26,29] and in disagreement with that of others [25].…”
Section: Discussionsupporting
confidence: 90%
“…The present study found a significant positive correlation between serum levels of TNF-a and PASI score (P = 0.03); this result is in agreement with that of some investigators [26,29] and in disagreement with that of others [25].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Kyolic aged garlic extract was found to significantly reduce the inflammatory marker TNF-alpha in hypertensive patients (3). High ratios of IL-6/ TNF-α were found relevant in the modulation of both innate and adaptive immune responses in newborns (24), and play a role in the etiology of a number of autoimmune diseases (25).…”
Section: Introductionmentioning
confidence: 99%